Methods for the investigation of systems of differential equations with pulse influence - Luchka, A. Y. (Ukrains’kyi Matematychnyi Zhurnal, 1998)
We establish consistency conditions for a system of differential equations with pulse influence and additional conditions. The applicability of approximate methods to problems of this type is justified.